2008
DOI: 10.1007/s12221-008-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Changing porosity of knitted structures by changing tightness

Abstract: A geometrical model of plain knitted structures is discussed in depth to understand the yarn path in a knitted loop. A theoretical model has been created to predict the porosity of a knitted structure depending on the geometrical parameters, such as course spacing, wale spacing, stitch length, fabric thickness, count of yarn and fibre density. Polyester and nylon plain knitted fabrics were produced to different tightness, and porosity was determined by measuring the weight. The validity of the model was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…If this relationship is maintained through a range of fabrics for a given knitted structure, then those fabrics are related in their tightness and other physical characteristics [9]. Dias and Delkumburewatte [14] studied the effect of fabric tightness or cover factor on porosity of knitted structures. This study demonstrated that there is a relationship between the stitch length, course spacing, wale (vertical stitch) spacing, fabric thickness, yarn count and fabric tightness.…”
Section: Introductionmentioning
confidence: 99%
“…If this relationship is maintained through a range of fabrics for a given knitted structure, then those fabrics are related in their tightness and other physical characteristics [9]. Dias and Delkumburewatte [14] studied the effect of fabric tightness or cover factor on porosity of knitted structures. This study demonstrated that there is a relationship between the stitch length, course spacing, wale (vertical stitch) spacing, fabric thickness, yarn count and fabric tightness.…”
Section: Introductionmentioning
confidence: 99%
“…It shows as the thickness decreases porosity increases. 19 It shows the linear relationship between thickness and porosity.…”
Section: Relationship Between Thickness and Porosity Is Followingmentioning
confidence: 95%
“…The plain-knit structure essentially consists of this unit cell repeating itself in both the length and the width directions. [17][18][19][20][21][22] In the research work on the review of literature, among other relevant topics, the geometrical structure and parameters of a plain knitted structure. The stitch length model proposed by Peirce is particularly discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity of a textile material is its ability to conduct heat through it. Thermal conductivity depends on the material and the porosity [14]. It is expressed as…”
Section: Measurement Of Structural and Comfort Parametersmentioning
confidence: 99%